2021
DOI: 10.3389/fmars.2021.739662
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Transcriptional Responses to Acute and Chronic Thermal Stress in the Ark Shell Scapharca subcrenata

Abstract: Ark shells (Scapharca subcrenata) grown on the tidal flats are often exposed to high temperature stresses in summer. In order to better understand their adaption to extreme or natural high temperature, we first determined the 96-h upper lethal temperature of ark shell and then investigated their physiological and transcriptional responses to acute or chronic thermal stress at the 96-h upper median lethal temperature (32°C). A significantly higher cumulative mortality (52% in 96 h) was observed in the acute hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…In the present study, induced CAT activity and higher Hdh-CAT mRNA expression levels were observed in response to thermal stress. Similar findings have been previously reported for CAT in scallop [4], ark shell [21], Mediterranean mussel [60], and Pacific oyster [61]. The present study also found elevated ROS levels in thermal-stressed abalone, consistent with previous findings of American oyster [31].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, induced CAT activity and higher Hdh-CAT mRNA expression levels were observed in response to thermal stress. Similar findings have been previously reported for CAT in scallop [4], ark shell [21], Mediterranean mussel [60], and Pacific oyster [61]. The present study also found elevated ROS levels in thermal-stressed abalone, consistent with previous findings of American oyster [31].…”
Section: Discussionsupporting
confidence: 93%
“…Temperature is a vital abiotic factor that can significantly affect the physiology of marine organisms [21]. In recent decades, seawater temperature has been rising with the acceleration of climate change [21,56].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results suggest that the warming of the sea is reflected in the physiological performance and ultimately the seasonal cycle in flesh weight of the ark shell in different manners between winter and summer: physiological benefits and advanced weight gain vs. heat stress and progressive weight loss (Ning et al, 2021;Zou et al, 2021), respectively. Our measurements revealed the absence of seasonal temperature acclimation in the physiological processes of A. kagoshimensis.…”
Section: Discussionmentioning
confidence: 87%